Treatment for Disruption of Smartphone Use in Learning Activity Through School-Wide Positive Behavior Support - Mufrihah, Arina (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
This study is purposed for guiding students to use their smartphone appropriately and opportunely through School-Wide Positive Behavior Support (SWPB). Location of this research was at SMA Muhammadiyah 1 Yogyakarta which used Classroom Action Research and Spiral Self-Reflective as its design. The research process was undertaken within 2 cycles where each cycle consists of the planning phase, action phase, and reflection phase. Group counseling and individual counseling were applied as the form of SWPB in which students who received these services were selected purposively. All data collected through observation, questionnaire, and interview. Respondents participated cooperatively during counseling service sessions; as a result, they can manage their selves to not use smartphone unless it is necessary for learning resource and assignment in the classroom.